O artystycznym i estetycznym pożytku z kategorii warstwy. Przyczynek do ontologii dzieła sztuki Nicolaia Hartmanna - Mordka, Artur (Wydział Sztuki UR, 2018)
The article attempts to analyze the aesthetic and artistic meaning of the layer category. The author has chosen it as the subject of his analysis, as it is part of the research on aesthetics by Nicolai Hartmann; however, it can also be used to clarify the creative process. The first part of the article discusses the notion of a layer that Hartmann uses, moving on to the considerations which include the unity of a work of art, its manner of existence and sensual (visual) appearance of irreal content.
On artistic and aesthetic benefits of the layer category. A contribution to Nicolai Hartmann’s ontology of a work of art
Keywords: Nicolai Hartmann; warstwa; dzieło sztuki; sztuka; ontologia; estetyka; jedność; jawienie; layer; art; work of art; ontology; aestheticism; unity; appearance